PENGARUH CARA PENGOLAHAN TEPUNG IKAN DARI LIMBAH INDUSTRI PENGOLAHAN IKAN NILA TERHADAP ENERGI METABOLISME PADA AYAM KAMPUNG - Jonathan Anugerah Lase (Universitas Sumatera Utara, 2014)
ABSTRACT JONATHAN ANUGERAH LASE,2O14 : “Influence Processing of Tilapia Fish Industry by Product Meal Metabolism Energy onLocal Chicken”. Under supervisied by MA’RUF TAFSIN and NURZAINAH GINTING. The research aimed to objective the influence of tilapia fish processing industry by product meal (LIPIN)metabolism Energy on local chicken. The research had been conducted in Compost Centre, Agriculture Faculty the Univesity of Sumatera Utara,starter August 2013 to November 2013. The design in this research used completely randomized design with 6 treatments and 4 replications. The treatments research consists of : commercial fish meal (R0), LIPIN meal pressed and drying with oven 40 0C(R1) and sunlight (R2), LIPIN non pressed anddrying with oven 40 0C (R3), non pressed and drying with sunlight (R4) and fermentation silage (R5). The result showed the best way processing of LIPIN in terms of metabolism energy, nitrogen retention, and energy conversion, stated that treatment no pressedwith drying oven 400C better than treatment pressed with drying sunlight, fermentation silage treatment better than treatment pressed and non pressed sun drying and 400C oven drying, and commercial fish meal quality is better than fish meal from LIPIN. The conclusion of this research is influence ways processing of tilapia fish industry by product meal take effect nitrogen retention, metabolism energy and metabolisc energy conversion off gross energy range local chicken feed. Keywords : Ways of processing, LIPIN, Metabolism Energy, Local Chicken.